2018
DOI: 10.1063/1.5008852
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of THz acoustic wave packets in GaN at room temperature

Abstract: We use femtosecond laser pulses to generate coherent longitudinal acoustic phonons at frequencies of 1–1.4 THz and study their propagation in GaN-based structures at room temperature. Two InGaN-GaN multiple-quantum-well (MQW) structures separated by a 2.3 μm-thick GaN spacer are used to simultaneously generate phonon wave packets with a central frequency determined by the period of the MQW and detect them after passing through the spacer. The measurements provide lower bounds for phonon lifetimes in GaN, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…While the generation and detection of THz coherent acoustic phonons has been a subject of considerable interest in prior literature (readers are referred to ref for a comprehensive overview of this topic), other works specifically focusing on direct lifetime measurements of subterahertz phonon modes have been limited to semiconductors based on InGaN/GaN SLs. In this regard, a recent work by Maznev et al has shown that 1–1.4 THz coherent acoustic phonons in GaN can propagate more than 2 μm with a lifetime of ∼136 ps measured for a 1.06 THz phonon mode at RT, which they ascribe as a lower bound due to both intrinsic and extrinsic scattering processes. Similarly, Liu et al measure an intrinsic phonon lifetime of ∼150 ps at 380 GHz, which the authors ascribe as dictated by three-phonon scattering processes.…”
Section: Resultsmentioning
confidence: 99%
“…While the generation and detection of THz coherent acoustic phonons has been a subject of considerable interest in prior literature (readers are referred to ref for a comprehensive overview of this topic), other works specifically focusing on direct lifetime measurements of subterahertz phonon modes have been limited to semiconductors based on InGaN/GaN SLs. In this regard, a recent work by Maznev et al has shown that 1–1.4 THz coherent acoustic phonons in GaN can propagate more than 2 μm with a lifetime of ∼136 ps measured for a 1.06 THz phonon mode at RT, which they ascribe as a lower bound due to both intrinsic and extrinsic scattering processes. Similarly, Liu et al measure an intrinsic phonon lifetime of ∼150 ps at 380 GHz, which the authors ascribe as dictated by three-phonon scattering processes.…”
Section: Resultsmentioning
confidence: 99%
“…This calculation method is the same as that previously published in Ref. [26]. four-phonon scattering is expected to also be negligible.…”
Section: Fig5mentioning
confidence: 95%
“…where is the phonon propagation time in the GaN spacer layer ( =288 ps for sample 1, while =141.3 ps for sample 2), is the intrinsic phonon lifetime in GaN, and the factor accounts for the temperature-independent attenuation such as GaN thickness non-uniformity [26], as well as scattering by sample imperfections. Since these extrinsic factors are strongly related to quality of the sample and may vary with the laser spot position, we used a diamond pen and scratched a pattern on the sample to define a reference position and used an optical microscope to in situ ensure that the laser spot was at the same position (relative to the reference position) during temperature-dependent measurements.…”
Section: Fig5mentioning
confidence: 99%
See 2 more Smart Citations